A classification of combined homicide‐suicide: An update—Part III: Extrafamilial homicide‐suicide - Felthous, Alan R.; Masood, Yasir; Safari, Delavar; Rodgers, Emily; Chennu, Navreet; Kahlon, Chanchal; Angly, Mary (Journal of forensic sciences, 2024)
The subclassification of homicide‐suicide into psychopathology and intrafamilial homicide‐suicides having been presented in the foregoing Parts I and II, this Part III concerns extrafamilial homicide‐suicides. Extrafamilial homicide‐suicides are divided into adversarial, autogenic mass, cult, and terrorist homicide‐suicides. Adversarial homicide‐suicides involve a “formal” relationship between actor and homicide victims, further divided according to the role of the actor in their relationship as employee, current or former pupil/student as in school shootings, patient, and litigant. For comparison, school shootings were divided into those resulting in 10 or more homicide victims and those with fewer. The autogenic mass homicide‐suicide, wherein victims are strangers to the actor, was heuristically bifurcated here depending on the number of homicide victims, 10 or more or fewer. As expected, the homicide‐suicides with larger numbers of victims were more homogenous.